Survival benefit after neoadjuvant or adjuvant radiotherapy for stage II–III gastroesophageal junction adenocarcinoma: A large population-based cohort study - Zuo, Zhichao; Peng, Yafeng; Zeng, Ying; Lin, Shanyue; Zeng, Weihua; Zhou, Xiao; Zhou, Yinjun; Li, Bo; Ma, Jie; Long, Mingju; Cao, Shenghui; Liu, Yang (Frontiers in Oncology, 2022)
Objective: The standard treatment for stage II-III gastroesophageal junction adenocarcinoma (GEJA) remains controversial, and the role of radiotherapy (RT) in stage II-III GEJA is unclear. Herein, we aimed to evaluate the prognosis of different RT sequences and identify potential candidates to undergo neoadjuvant RT (NART) or adjuvant RT (ART). Materials and Methods: In total, we enrolled 3492 patients with resectable stage II–III GEJA from the Surveillance, Epidemiology, and End Results (SEER) database, subsequently assigned to three categories: T1-2N+, T3-4N-, and T3-4N+. Survival curves were evaluated using the Kaplan-Meier method along with the log-rank test. We compared survival curves for NART, ART, and non-RT in the three categories. To further determine histological types impacting RT-associated survival, we proposed new categories by combining the tumor, node and metastasis (TNM) stage with the Lauren classification. Results: ART afforded a significant survival benefit in patients with T1-2N+ and T3-4N+ tumors. In addition, NART conferred a survival advantage in patients with T3-4N+ and T3-4 exhibiting the intestinal type. Notably, ART and NART were both valuable in patients with T3-4N+, although no significant differences between treatment regimens were noted. Conclusions: Both NART and ART can prolong the survival of patients with stage II–III GEJA. Nevertheless, the selection of NART or ART requires a concrete analysis based on the patient’s condition.